Mengajarkan Bahasa Pemrograman Python Di Tingkat SMA Untuk Meningkatkan Manajemen Sumber D aya Manusia - Muhammad, Muhammad (Universitas Malahayati, 2021)
Technology rather than becoming producers, both hardware and software. Indonesia also has ashort age of programmers, thus many programmers from India and the Philippines work inIndonesia. Interms of hardware, Indonesia seems difficult to competein the short and medium termwith countries that have an established electronics industry culture. Butin the field of softwareIndonesia has agre at opportunity, if Indonesia can educateas many human resources as possible toenable them to write programming code. Allthistime, most Indonesians have tended to only learn touse applied software (applications) that are on the outer layer, it is far from the core of computerscience, so they are unable to control computers outside of the frame work created by theapplication maker. The increasingly close combination of information and communicationtechnology allows large companies to control computer networks from outside the traditionaljurisdiction of a country. As a result, computer users in Indonesia are unable to control the use ofcomputer networks for national interests and are at risk of being trapped in applied programscreated by foreign companies.Keywords ; programm, hardware, python, human resource